2017
DOI: 10.1108/intr-05-2016-0140
|View full text |Cite
|
Sign up to set email alerts
|

The joint effect of association-based corporate posting strategy and eWOM comment valence on social media

Abstract: Purpose -Consumers tend to form their perceptions about a company via two associations: corporate ability (CA) that centers on expertise in producing quality products and corporate social responsibility (CSR) that focuses on societal obligations. To date, investigations on the adoption of such association-based corporate communication strategies are yet to address the interactive and multi-source features of social media. Drawing theoretical insights from corporate associations and the warranting principle, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Online community member's satisfaction is one of the leading motivational drivers towards e-WOM. However, online community members purchasing decisions are always hugely influenced by what others say (44)(45)(46). The value of e-WOM lies among the online community groups is actively engaged by exchanging information with families, friends, colleagues, and strangers without avail any money (47).…”
Section: Social Currency In Terms Of E-word Of Mouth (E-wom)mentioning
confidence: 99%
“…Online community member's satisfaction is one of the leading motivational drivers towards e-WOM. However, online community members purchasing decisions are always hugely influenced by what others say (44)(45)(46). The value of e-WOM lies among the online community groups is actively engaged by exchanging information with families, friends, colleagues, and strangers without avail any money (47).…”
Section: Social Currency In Terms Of E-word Of Mouth (E-wom)mentioning
confidence: 99%
“…OGB consumers may also provide individual narrative assessment of their experiences about service deals via electronic word-of-mouth (e-WOM) by using different Internet platforms (outside the OGB website), such as online reviews at blogs, video logs (e.g., on YouTube), personal emails to friends and family, and bulletin board systems. Existing non-OGB research has found that these forms of UGC, whether aggregated or not, are effective in influencing online buyers intentions (Chen et al ., 2017; Chong et al ., 2018; López-López and Parra, 2016; Teng et al ., 2017).…”
Section: Notesmentioning
confidence: 99%
“…Social media forums are a useful way for online users to share opinions (Chen, 2017), to obtain information about products and services (Lin and Xu, 2017;Bijmolt et al, 2014), as well as to discuss political issues (Kwon and Gruzd, 2017). They are also an essential channel for word-of-mouth marketing ( Jalilvand and Samiei, 2012;Gvili and Levy, 2016;Chen et al, 2017;Choi et al, 2017;Ortiz et al, 2017;Xun and Guo, 2017).…”
Section: Related Workmentioning
confidence: 99%